2017
DOI: 10.14302/issn.2638-4469.japb-17-1838
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Analysis of Fragaria Vesca MLO Genes Involved in Interaction with Powdery Mildew (Podosphaera Aphanis)

Abstract: Strawberry powdery mildew, caused by Podosphaera aphanis is a major fungal disease that affects strawberry yield and quality. In the model plant species Arabidopsis and the crop plants barley, tomato and pea, the Mildew resistance locus O (MLO) proteins have been found to be required for powdery mildew susceptibility.The present study, based on the sequence of a wild plum (Prunus americana) MLO protein, identified 16 MLO genes within the genome of woodland strawberry, Fragaria vesca and examined their express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Transcriptome analysis has shown differentially expressed genes (DEGs) related to secondary metabolism, signal transduction, and disease resistance were upregulated and played crucial roles in the early defence against P. aphanis [18]. Furthermore, functional identification of candidate genes from the diploid strawberry has enabled the investigation of resistance to P. aphanis, including FvHsfB1a [19], FvMLO [20], and FvWRKY42 [21]. Antisense expression of PpMlo1-conferred resistance in the octoploid strawberry to P. aphanis, indicating that the Mlo-based resistance mechanism is functional in strawberry [22].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome analysis has shown differentially expressed genes (DEGs) related to secondary metabolism, signal transduction, and disease resistance were upregulated and played crucial roles in the early defence against P. aphanis [18]. Furthermore, functional identification of candidate genes from the diploid strawberry has enabled the investigation of resistance to P. aphanis, including FvHsfB1a [19], FvMLO [20], and FvWRKY42 [21]. Antisense expression of PpMlo1-conferred resistance in the octoploid strawberry to P. aphanis, indicating that the Mlo-based resistance mechanism is functional in strawberry [22].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Pessina et al [10] reported that knock-down expression of the MLO gene MdMLO19 in apple reduced the susceptibility of transformed lines to powdery mildew, and Jiwan et al [11] reported that antisense expression of the peach MLO gene PpMLO1 in transgenic cultivated strawberry lines conferred resistance to Fragaria -specific powdery mildew isolates. Recently, two groups [12,13] characterised several MLO genes and pseudogenes in the genome sequence of F . vesca .…”
Section: Introductionmentioning
confidence: 99%
“…Twelve of the identified genes were expressed following challenge by isolates of powdery mildew in F . vesca accessions [13]. Two of these genes, annotated as FvH4_7g08130.1 and FvH4_7g19790.1 in the FvH4 v4.0 assembly [14], were differentially expressed in response to powdery mildew infection in F .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, functional identification of candidate genes from the diploid strawberry has enabled the investigation of resistance to P. aphanis. These include FvHsfB1a [19], FvMLO [20], and FvWRKY42 [21]. Antisense expression of PpMlo1 conferred resistance in the octoploid strawberry to P. aphanis, indicating that the Mlo-based resistance mechanism is functional in strawberry [22].…”
Section: Introductionmentioning
confidence: 99%